Antibacterial Activity Of Staphylococcus aureus From Chinese Betel Leaf Juice (Peperomia pellucida L.) - Wantah, Kezia T.; Kanter, Jabes W.; Tulandi, Selvana S.; Mongi, Jeane; Palandi, Reky R.; Pakingki, Priska (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2024)
Infectious diseases, especially in developing countries such as Indonesia, are a common health problem, one of which is caused by bacteria. This study tested the antibacterial activity of Chinese betel leaf extract against Staphylococcus aureus bacteria, with secondary metabolite content such as alkaloids, tannins, and flavonoids that act as antibacterials. This study was a laboratory experiment using a completely randomized design with three repetitions at five concentrations of extract, as well as one positive and negative control. The method used was the agar diffusion method, and the test results showed that Chinese betel leaf extract had antibacterial potential against Staphylococcus aureus at various concentrations tested. The concentrations used were 6µL/disc, 8µL/disc, 10µL/disc, 12µL/disc, and 14µL/disc, where all these categories produced inhibition zones included in the moderate category according to Susanto (2012). Statistical analysis using the Kruskal-Wallis test produced a significant value of 0.035 (<0.05), indicating a significant difference between each concentration tested. From the research results, it can be concluded that Chinese betel leaf extract has effective antibacterial activity against Staphylococcus aureus.